Relationship of the recurrence after pterygium surgery with the presence of HSV, EBV, CMV, HPV, and BRAFV600E mutation - S.O. Rykov; K.O Usenko; S.Iu. Mogilevskyy; S.V. Ziablitsev; L.I. Denisiuk (Ukrainian Society of Ophthalmologists, 2019)
Background: Previously, we have reported on associations of pterygium with the presence of herpes simplex virus (HSV), Epstein Barr virus (EBV), cytomegalovirus (CMV), human papillomavirus (HPV), and the BRAFV600E somatic point. The current study attempted to examine the relationship between the recurrence during 1 year after pterygium surgery and the presence of these factors. Purpose: To identify the relationship between (a) recurrence rates after various surgical techniques for pterygium and (b) the presence of herpes viruses (HSV, EBV, and CMV), HPV 6, 11, 16 and 18 and BRAFV600E mutation. Materials and Methods: Two hundred and three patients (232 eyes) with a history of pterygium surgery underwent examination. They were divided into five groups based on the method of surgical treatment: Group 1 (the McReynolds transplantation only) of 49 eyes; Group 2 (the McReynolds transplantation, with adjuvant MMC 0.02% applied to the cornea for 30 sec) of 41 eyes; Group 3 (the technique of Arlt) of 49 eyes; Group 4 (the technique of Arlt, with adjuvant MMC 0.02% applied to the cornea for 30 sec) of 46 eyes; Group 5 of 47 eyes that were treated with our technique of pterygium excision involving the growth plate, with conjunctival autoplasty and adjuvant MMC 0.02%. Real-time PCR with PCR kits from DNK Tekhnologiya (Russia) were used to identify HSV, EBV, CMV, and HPV. PCR amplification was performed in a DT-lite real-time PCR system (DNK Tekhnologiya). Mutation detection was performed using TaqMan Mutation Detection Assays (Thermo Fisher Scientific) in a Real-Time PCR System 7500 (Applied Biosystems, USA). Results: Changing from traditional surgical methods (the McReynolds or Arlt method, alone or with adjunctive mitomycin C) to our methodology for pterygium decreased the recurrence rate at 1 year after pterygium surgery by 17.0% (or 2.1-fold), from 31.9% to 14.9% (χ2 = 5.32; р = 0.021). There was a common trend regarding the relationship between the presence of BRAFV600 mutation and pterygium recurrence in the groups: in the groups with traditional surgical methods, the recurrence rate in BRAFV600 mutation-positive patients varied from 73.3% to 81.2%, whereas the recurrence rate in BRAFV600 mutation-negative patients varied from 4.2% to 10.7% (p < 0.001). The mutation increased the risk of a recurrence within a year after pterygium surgery approximately 35.7-fold (OR=35.72; 95% CI, 15.71-81.24). Changing from traditional surgical methods to our methodology for pterygium decreased the recurrence rate at 1 year after pterygium surgery in BRAFV600 mutation-positive patients by 39.8% (or 2.1-fold), from 77.3% to 37.5% (χ2 = 116.92; р < 0.01). Statistical analysis found no relationship between the distribution of recurrences among the groups, and presence of either individual viruses or their combinations (p > 0.1 for all cases). Conclusion: The presence of HSV, EBV, CMV, HPV, and/or BRAFV600 mutation in pterygium tissue is a risk factor for recurrence after surgical treatment.